Promocja „Powieści moralnych” Jean‑Françoisa Marmontela - Hombek, Danuta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The present article discusses in chronological order various forms of promoting Powieści moralneby Jean‑François Marmontel. Since the seventies of the 18th century, it was well‑known French‑Varsovian publisher and bookseller Piotr Dufour who undertook to print and promote the work concerned. However, his attempts to arouse the interest in the publication among the readers proved, in fact, not much successful. Powieści moralne shared a similar fate of many other publications of the Enlightenment period – they were laying useless at the booksellers yet for many years after being published.